A Literature Review on the Internalization of Qur’anic Values through Religious Activities in Building Students’ Religious Character at Islamic Elementary Schools (MI) - Suparlan (Formad English Foundation NTB Jakarta, 2025)
This study is motivated by the limited systematic research on the internalization of Qur’anic values through religious activities in Madrasah Ibtidaiyah (MI), despite its significant impact on the formation of students’ religious character in Islamic elementary education. The study aims to analyze the concepts and forms of Qur’anic value internalization, to identify strategies, models, and pedagogical approaches employed in previous studies, and to examine supporting and inhibiting factors influencing the process of religious character formation in MI. This research adopts a qualitative literature review design, focusing on peer-reviewed journal articles and scholarly books published primarily within the last ten years. Relevant studies were selected through purposive sampling based on their alignment with Qur’anic value education, religious activities, and character development in Islamic elementary schools. Data were collected through systematic documentation and analyzed using thematic content analysis to synthesize patterns, relationships, and theoretical insights. The findings reveal that the internalization of Qur’anic values is predominantly understood as a gradual and multidimensional process integrating cognitive, affective, and behavioral domains. Religious activities—such as congregational prayers, Qur’an recitation, memorization programs, and school culture–based practices—function as the main mediating instruments of value transmission. Habituation and teacher exemplification emerge as dominant strategies, supported by integrative and holistic school-based models. However, the process is influenced by both supporting factors, including teacher competence and family–school alignment, and inhibiting factors, such as limited instructional time and external socio-digital influences. The study concludes that effective Qur’anic value internalization requires systemic, continuous, and contextually reinforced efforts across school, family, and community settings. The findings contribute theoretically to Islamic character education literature and offer practical implications for educators and institutions in strengthening sustainable religious character formation. Future research is recommended to employ empirical and longitudinal approaches to deepen understanding of this phenomenon.